LA GERENCIA DE PROYECTOS: BASE DEL DESARROLLO DE UN PAÍS EN EL SIGLO XXI - Portocarrero Chávez, Victor (2005)
The importance of the management of projects is reflected in the necessity that the developed emerging countries have in the XXI century in its effective application , with which one can plan the future, elaborating its development plans to médium term and in turn ‘creating its future‘, executing its plans by means of programs through the Project Management. The importance of elaborating and executing investment projects in both public and private context, in any part of the world is of obligatory character if we don‘t want to stay blocked. For this reason we expose the fundamental role of the management of project in the development of the countries, especially in our country whose economic growth is so complicated in these times of globalization.